Catheter closure of the arterial duct in preterm infants. Issue 4 (18th August 2006) - Roberts, Philip; Adwani, Satish; Archer, Nick; Wilson, Neil
Abstract : Background: When medical treatment of a symptomatic arterial duct in a preterm infant fails, management is surgical. Patients and Methods: 10 preterm neonates referred to a tertiary cardiac centre for treatment of a symptomatic patent arterial duct who underwent cardiac catheterisation with the intention of device closure. Results: Successful catheter device closure of the arterial duct in nine preterm infants is described. Conclusion: In selected cases, catheter device closure may offer an alternative to thoracotomy and surgical ligation.